2009
DOI: 10.1007/s10620-009-0816-2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphisms of CYP2D6 Oxidation in Patients with Inflammatory Bowel Disease

Abstract: Inflammatory bowel disease (IBD) consists of ulcerative colitis and Crohn's disease, both of which are associated with increased colorectal cancer risk. The relationship between genetically determined polymorphic metabolism of exogenous substances by oxidation catalyzed by CYP2D6 isoenzyme and susceptibility to cancer has aroused great interest. We determined whether there was an association between susceptibility to inflammatory bowel disease and particularly to CYP2D6 genotypes. The study was carried out in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…They announced that despite the fact that the odds ratio (OR) was higher in carriers of the CYP2D6*1 /CYP2D6*3 genotype [extensive metabolizer (EM)], there was no factually significant difference in the recurrence of the CYP2D6 alleles in patients with UC and CD. Similarly, Trzcinski et al[60] have shown that the increased OR for inflammatory bowel disease (IBD) was without statistical significance. These researches suggest that there were no measurably significant variations in the appearance of the CYP2D6 alleles in IBD patients (UC or CD).…”
Section: Cyp2d6mentioning
confidence: 99%
“…They announced that despite the fact that the odds ratio (OR) was higher in carriers of the CYP2D6*1 /CYP2D6*3 genotype [extensive metabolizer (EM)], there was no factually significant difference in the recurrence of the CYP2D6 alleles in patients with UC and CD. Similarly, Trzcinski et al[60] have shown that the increased OR for inflammatory bowel disease (IBD) was without statistical significance. These researches suggest that there were no measurably significant variations in the appearance of the CYP2D6 alleles in IBD patients (UC or CD).…”
Section: Cyp2d6mentioning
confidence: 99%
“…Several factors -genetic, environmental, immunological and psychological -have been implicated in initiation and development of IBD [1][2][3][4][5][6]. Recently, scientific efforts have concentrated on polymorphisms of the proteinencoding genes that contribute not only to the immune response (NOD2/CARD15, Hp) but also to detoxification reactions (PON1, PON2, NAT2, CYP2D6) [1,[7][8][9][10]. Thus, mutations in the ABCB1/MDR1 (ATP-binding cassette subfamily B member 1/multidrug resistance 1) gene have also been assessed as a potential factor that may affect the development of IBD.…”
Section: Introductionmentioning
confidence: 99%